2013
DOI: 10.1074/jbc.m112.426999
|View full text |Cite
|
Sign up to set email alerts
|

The Oncogene HER2/neu (ERBB2) Requires the Hypoxia-inducible Factor HIF-1 for Mammary Tumor Growth and Anoikis Resistance

Abstract: Background: Oncogene HER2 (ERBB2) regulates breast cancer growth and anoikis resistance. Results: ERBB2 requires hypoxia-inducible factor (HIF)-1 for breast cancer growth in vivo and anoikis resistance in vitro. Conclusion: HIF-1 plays a critical role in ERBB2-positive breast cancers. Significance: Genes co-regulated by ERBB2 and HIF-1 may be novel therapeutic targets for treating breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 47 publications
(70 reference statements)
5
55
2
Order By: Relevance
“…Previous studies have linked multiple, distinct members of the Bcl-2 family to ERK-mediated inhibition of anoikis (13,27,28,30,(37)(38)(39). Therefore, we looked for differences in the expression of either pro-apoptotic (e.g.…”
Section: Aggregate Formation Facilitates Anoikis Evasion In E-cadherimentioning
confidence: 99%
“…Previous studies have linked multiple, distinct members of the Bcl-2 family to ERK-mediated inhibition of anoikis (13,27,28,30,(37)(38)(39). Therefore, we looked for differences in the expression of either pro-apoptotic (e.g.…”
Section: Aggregate Formation Facilitates Anoikis Evasion In E-cadherimentioning
confidence: 99%
“…[18][19][20] Interestingly, previous studies have shown that ErbB2 and EGFR, which are hyperactivated in a substantial percentage of IBC patients, 21 can effectively antagonize the anoikis program to facilitate anchorage-independent growth. [22][23][24][25][26][27][28] However, a detailed examination of the molecular mechanisms underlying anoikis inhibition in IBC cells has yet to be completed. In this study, we demonstrate that signaling from EGFR and ErbB2 through ERK/MAPK has a major role in the ability of IBC cells to survive in the absence of ECM attachment.…”
mentioning
confidence: 99%
“…The less strong effect in increasing mRNA/protein expression of Bid, Bim and Puma induced by the MAPK pathway inhibitor PD98059 might be related with other activating/inhibiting signal pathway like hypoxia-inducible factor-1a (HIF-1a) activated by sevoflurane post-conditioning [2]. Some studies showed that HIF-1a inhibits transcriptions of Bid, Bim and Puma gene that may help cells to adapt to hypoxic/ischemic circumstances [30][31][32][33]. An essential axis of activation of Bid, Bim, Puma-BAX and BAK was correlated with activating the mitochondrial death program, which could offer common ground for therapeutic interventions [8].…”
Section: Discussionmentioning
confidence: 96%